Are lithium niobate (LiNbO3) and lithium tantalate (LiTaO3) ferroelectrics bioactive? - Vilarinho, Paula Maria
The use of functional materials, such as ferroelectrics, as platforms for tissue growth in situ or ex situ, is new and holds great promise. But the usage of materials in any bioapplication requires information on biocompatibility and desirably on bioactive behavior when bone tissue engineering is envisaged. Both requirements are currently unknown for many ferroelectrics. Herein the bioactivity of LiNbO3 and LiTaO3 is reported. The formation of apatite-like structures on the surface of LiNbO3 and LiTaO3 powders after immersion in simulated body fluid (SBF) for different soaking periods indicates their bioactive potential. The mechanism of apatite formation is suggested. In addition, the significant release of lithium ions from the ferroelectric powders in the very first minutes of soaking in SBF is examined and ways to overcome this likely hurdle addressed. (C) 2014 Elsevier B.V. All rights reserved.